The Role of Teachers in Instilling The Values of Rights and Obligations in Students - Febriola, Sahara (Berpusi Publishing, 2025)
Education has a crucial role in shaping individual character and morals, with teachers as the spearhead in this process. However, the values of rights and obligations are often overlooked in an increasingly complex society, influenced by external factors such as social media and popular culture. This research uses a literature review method to explore the role of teachers in instilling the values of rights and obligations in students, overcoming the challenges they face, as well as strategies for transferring these values to students with diverse backgrounds. The results show that teachers play an important role as behavior models, learning facilitators, moral guides, and creativity developers. Effective strategies include integrated character education, being critical of social media, forming partnerships with parents, and using technology wisely. In collaboration between teachers, parents, and the school environment, parent-teacher meetings, family education programs, and the formation of a positive school culture are the keys to instilling the values of rights and obligations. With strong understanding and collaboration, it is hoped that a generation will be created that has high moral awareness and strong social responsibility to build a better society in the future.